Ecological solidified soil integrating scouring protection and seaweed restoration and preparation method of ecological solidified soil
Through the combination of ecological solidified soil materials, the contradiction between seabed protection and ecological restoration was resolved, the simultaneous germination and colonization of seagrass seeds was achieved, the efficiency of seagrass bed restoration was improved, adaptation to the marine environment was achieved and costs were reduced.
Patent Information
- Application Number
- CN202510824830.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-10-14
AI Technical Summary
The density of existing seabed protection materials is inconsistent with the growth requirements of seagrass, the seed delivery process is not compatible, and the protection and ecological restoration functions are separated, resulting in low efficiency of seagrass bed restoration and mismatch of engineering protection cycles.
An ecological solidified soil is used, whose components include sea mud, coral sand, modified chitosan gelling agent, silicate geopolymer, slow-release nutrient ceramsite, seaweed seeds and microbial carriers. Through the synergistic effect of the material components, an anti-scour protection layer is formed and the in situ germination and colonization of seaweed seeds are promoted.
It achieves the synchronization of seabed scour protection and ecological restoration, improves the germination rate and root density of seagrass seeds, reduces the cost of management, adapts to the marine environment, and has the characteristics of environmental friendliness and low cost.
Smart Images

Figure BDA0005457760950000051 
Figure BDA0005457760950000061 
Figure HDA0005457760970000011
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the cross field of marine engineering materials and ecological restoration technology, in particular to an ecological protection method based on scour protection and integrated ecological solidified soil for seaweed restoration, and belongs to the collaborative innovation technology of marine environmental engineering and ecological material science. BACKGROUND
[0002] As an important marine ecosystem, seaweed bed has irreplaceable ecological value in carbon sequestration, biological habitat maintenance, and coastal protection. However, due to human activities and marine environmental degradation, the global area of seaweed bed degradation has exceeded 30%. Current seaweed bed restoration mainly uses plant transplantation and seed direct sowing methods, but the former has low survival rate and destroys the original substrate, and the latter has a seed loss rate of 60-80% due to underwater current scouring, and the germination rate of naked seeds in poor substrates is less than 20%.
[0003] At the same time, traditional underwater protection engineering mainly uses riprap slope protection, concrete block, and other hard structures, which can effectively resist scouring, but the dense structure blocks the development of seaweed roots, making it difficult to combine ecological function and engineering protection. In recent years, dredged sludge solidified soil technology has been tried to be applied to underwater foundation reinforcement, which realizes soil stability through cement-based material solidification. However, existing solidified soil materials often control the porosity below 15% in pursuit of mechanical strength, making it difficult for seaweed seeds to attach and germinate in the solidified layer.
[0004] The above defects show that the existing technology faces three major bottlenecks in the field of underwater protection and seaweed bed ecological restoration: ① There is a fundamental contradiction between the high density of solidified materials and the porous needs of seaweed growth; ② The seed delivery process lacks adaptability to underwater hydrodynamic conditions, making it difficult to achieve precise positioning, and the phenomenon of secondary migration of seeds caused by the turbulence field in the restoration area is particularly serious; ③ The protection structure and ecological restoration function are separated, leading to a mismatch between the engineering protection period and the plant growth period, and the difference in material thermal expansion caused by the diurnal temperature difference in the intertidal zone further amplifies this non-coordinated effect. Therefore, it is urgent to develop a collaborative technology that can simultaneously achieve underwater scour protection and ecological restoration, and the present application is proposed in this background. SUMMARY
[0005] The present application aims at the problem that traditional marine engineering materials cannot consider both scour protection and ecological restoration, and provides a new type of ecological solidified soil which can be directly pumped to the seabed after being mixed with seaweed seeds, can form a scour protection layer, and can realize in-situ germination and planting of seaweed seeds, thereby synchronously solving the problems of seabed bed stability and seaweed bed ecological restoration. The solidified soil has a slump degree of 150-220 mm, a flow value of ≥180 mm, underwater anti-dispersion and self-leveling properties; an initial setting time of 6-12 hours, facilitating underwater construction adjustment; a 7-day compressive strength of ≥0.3 MPa and a 28-day strength of ≥1.0 MPa, capable of resisting scour at a flow rate of 2.5 m / s. In combination with the environmental characteristics of high salt, low light and frequent water disturbance of the seabed, the material components work synergistically to solidify the seabed surface while creating a stable germination microenvironment for seaweed seeds and promoting the natural succession of seaweed communities. The technology is applicable to the intertidal zone to an area with a water depth of 0.5-15 meters, and is particularly suitable for typical submerged plant seeds such as Zostera marina, Thalassia hemprichii and Halophila ovalis, and can adapt to a sea environment with a salinity of 28-35‰ and a water temperature of 10-30℃, and is applicable to a water body with a wave height of ≤2.5 meters and a turbidity of ≤50 NTU.
[0006] The object of the present application can be achieved by the following technical solutions:
[0007] An ecological solidified soil for seabed scour protection and ecological restoration, characterized in that the components of the solidified soil are proportioned by weight as follows: base material: 800-1000 parts of sea mud (moisture content 20%-35%) and 200-400 parts of coral sand (particle size 0.5-5 mm); solidified agent: 50-150 parts of modified chitosan gelling agent and 100-200 parts of silicate geopolymer; ecological functional component: 100-250 parts of slow-release nutrient ceramic and 50-120 parts of seaweed seeds; auxiliary additive: 80-160 parts of seawater activator and 20-50 parts of microbial carrier (loading salt-tolerant bacteria).
[0008] Preferably, the base material comprises the following components:
[0009] The sea mud is intertidal sediment, has an organic matter content of 3%-8% and a pH of 7.5-8.5; the coral sand is calcined at 800-1000℃, has a porosity of ≥40% and a specific surface area of ≥15 m 2 / g.
[0010] Preferably, the solidified agent comprises: 50-150 parts of modified chitosan gelling agent (degree of deacetylation ≥85%) and 100-200 parts of silicate geopolymer (fly ash / slag complex).
[0011] Preferably, the modified chitosan gelling agent is prepared by dissolving chitosan with a degree of deacetylation of ≥85% in a 2% acetic acid solution, adding maleic anhydride (molar ratio of chitosan to anhydride 1:0.15-0.25), and reacting at 50-60°C for 4-6 hours; after dialysis, freeze-drying is performed to obtain carboxylated chitosan; the carboxylated chitosan is reacted with glycidyltrimethylammonium chloride (molar ratio 1:0.3-0.5) at pH 8.0-8.5 for 12-24 hours to prepare the zwitterionic chitosan gelling agent.
[0012] Preferably, the silicate geopolymer is prepared by mixing fly ash and slag at a mass ratio of 2:1, grinding to a specific surface area of ≥400 m 2 / kg, adding an 8-12 mol / L NaOH solution (liquid-solid ratio 0.3-0.5), stirring and solidifying at 50-70°C for 12-24 hours; steam curing at 60°C for 48 hours, crushing and sieving to a particle size of ≤100 μm to obtain the silicate geopolymer.
[0013] Preferably, the ecological functional components include: slow-release nutrient ceramic: made by coating zeolite with seaweed extract, particle size 2-8 mm, nitrogen, phosphorus, and potassium slow-release period ≥90 days; seagrass seeds: salt-tolerant Thalassia hemprichii, Enhalus acoroides, and Hypnea musciformis seeds, 30-day cumulative germination rate ≥80%.
[0014] Preferably, the slow-release nutrient ceramic is prepared by first crushing natural zeolite to a particle size of 1-3 mm, soaking in 5% hydrochloric acid for 2 hours to remove impurities and open the pore structure, washing with water to neutralize, and then drying and calcining at 600°C for 2 hours to form a porous framework, significantly increasing the specific surface area to ≥300 m 2 / g; then preparing seaweed extract by crushing brown algae and mixing with deionized water at a ratio of 1:10, adding 0.5% cellulase for enzymatic hydrolysis at 50°C for 4 hours, and centrifuging and concentrating to obtain a viscous polysaccharide extract with a solid content of ≥20%; finally, through a coating process, the pretreated zeolite is immersed in the seaweed extract (mass ratio 1:1.5) for vacuum adsorption for 30 minutes, dried at 80°C, and then instantaneously calcined at 300°C for 5-10 minutes to form a stable coating layer, finally obtaining nutrient ceramic with both porous structure and slow-release performance.
[0015] Preferably, the seagrass seeds are prepared by first selecting Zostera marina, Thalassia hemprichii, or Halophila ovalis seeds, with a seed size of 1.5-3.0 mm, and using a 3% NaCl solution to sink to a retention density of ≥1.1 g / cm 3live seeds; then, germination pretreatment is carried out, the seeds are immersed into a composite liquid containing gibberellin acid (GA3, 100 mg / L) and 0.1% chitosan, and the seeds are treated at 25 DEG C in dark for 24 hours, and then dried to a water content of less than or equal to 8%; finally, a microbial coating process is implemented, the seeds are mixed with a suspension of Azotobacter and Pseudomonas at a mass ratio of 1:2 (bacterial concentration is greater than or equal to 10 8 CFU / mL), and the mixture is dried by blowing air at 40 DEG C to form a microbial-chitosan coating layer with the functions of nitrogen fixation and phosphorus solubilization, and the final coating rate is greater than or equal to 15%.
[0016] Preferably, the auxiliary additives include: seawater activator (sulfate activator and biological enzyme complex) 80-160 parts; microbial carrier (porous diatomite loaded with Azotobacter and Pseudomonas) 20-50 parts.
[0017] Preferably, the seawater activator is prepared as follows: firstly, sodium sulfate (Na2SO4) and calcium sulfate dihydrate (CaSO4·2H2O) are mixed at a mass ratio of 3:1, and then ground to a particle size of less than or equal to 50 microns; then, the mixture is calcined at a high temperature of 400-500 DEG C for 2 hours to generate a composite sulfate activator with a SO3 content of greater than or equal to 35% through a phase change reaction of calcium sulfate; then, a protease with an enzyme activity of greater than or equal to 5000 U / g and a lipase with an enzyme activity of greater than or equal to 3000 U / g are mixed at a ratio of 1:1, and then spray-dried with the composite sulfate activator at a mass ratio of 1:5 to finally obtain an enzyme-sulfate composite activator with the functions of inorganic activation and biological catalysis. The process strengthens the reaction activity of the sulfate system through high-temperature calcination, and forms a synergistic activation system by combining the specific catalytic function of biological enzymes.
[0018] Preferably, the microbial carrier is prepared as follows: firstly, diatomite is pretreated, the diatomite is soaked in 10% hydrochloric acid for 4 hours to remove impurities, and then dried after washing to neutral; the diatomite is calcined at 600 DEG C for 3 hours to form a porous carrier (porosity is greater than or equal to 60%, specific surface area is greater than or equal to 200 m 2 / g); then, Azotobacter vinelandii and Pseudomonas fluorescens are mixed at a volume ratio of 1:1 (bacterial concentration is greater than or equal to 10 8 CFU / mL); then, the mixed bacterial solution is mixed with the pretreated diatomite at a mass ratio of 1:2, and oscillated for 6 hours at 35 DEG C; finally, free bacteria are removed by centrifugation, and the loaded microbial carrier is obtained by vacuum drying at 40 DEG C (loading rate is greater than or equal to 90%).
[0019] The ecological adaptability is realized by the following multi-stage pH regulation system.
[0020] (1) The residual alkalinity of NaOH solution in the silicate geopolymer reacts with the CaO component of the calcined product of coral sand to generate Ca(OH)2, dynamically neutralizing the chitosan acidification residue;
[0021] (2) The porous zeolite framework in the slow-release nutrient ceramic adsorbs excess OH- through ion exchange, stabilizing the pore fluid pH fluctuation ≤±0.3;
[0022] (3) The surface silicon hydroxyl (Si-OH) of diatomite in the microbial carrier forms a pH buffer system with the sulfate in the seawater activator, maintaining the balance between microbial activity and seed germination requirements.
[0023] The advantages of the present application are:
[0024] (1) Integration of ecological and engineering functions. For the first time, the anti-erosion performance and seagrass ecological restoration function are integrated into a single material, breaking through the limitations of traditional engineering materials that only focus on mechanical protection, achieving simultaneous "protection-restoration", and reducing the comprehensive cost of coastal zone governance.
[0025] (2) Outstanding environmental adaptability. High-salt environment adaptation: through the ionic cross-linking action of the modified chitosan gelling agent, the solidified soil can still maintain stable hydration reaction when the seawater ion concentration is ≥35‰; Dynamic water flow tolerance: the three-dimensional network structure formed by silicate geopolymer and calcium carbonate whiskers improves the anti-dispersion by more than 50%, and can withstand long-term erosion at a flow rate of 2.5-3.0 m / s; Low light response mechanism: the seaweed polysaccharide component in the slow-release nutrient ceramic promotes seagrass seed energy metabolism under weak light conditions (illumination ≤1000 lux), and the germination rate is increased by 40% compared with traditional seeding.
[0026] (3) Long-term ecological gain. Nutrient precise regulation: seaweed-coated zeolite ceramic releases nitrogen, phosphorus, and potassium in a gradient (30% in the first 30 days, 70% in the next 60 days), highly matching the seagrass growth cycle; Microbe-plant synergy: diatomite carrier loaded with nitrogen-fixing bacteria / phosphorus-solubilizing bacteria continuously releases bioactive substances (such as IAA, siderophores), increasing seagrass root density by 2-3 times and accelerating the formation of meadow communities.
[0027] (4) Resource recycling and low cost. Coral sand substrate utilization rate ≥95%: direct use of intertidal zone sediments and coral waste, reducing raw material transportation costs and environmental disturbance; Low-temperature preparation process: geopolymer reaction temperature ≤70℃, low energy consumption; Construction efficiency doubled: self-leveling characteristics support ship-mounted pumping construction, with a single day paving area of 500-800 m 2 , 10 times higher efficiency than manual paving.
[0028] (5) Environmental friendliness is outstanding. Zero toxicity release: all components (such as modified chitosan, seaweed extract) are biodegradable materials, and the 28-day water leaching EC50 (luminescent bacteria) is ≥10000 mg / L, which is much higher than the environmental protection standard; carbon sequestration effect: the carbonate minerals generated by the solidification reaction of the coral sand base material and the carbon dioxide ≥50 kg per cubic meter of material can achieve negative carbon emissions.
[0029] (6) Intelligent response mechanism. pH self-regulation: the microbial carrier dynamically regulates the local pH (7.8-8.3) through nitrogen fixation / phosphorus solubilization metabolism, avoiding the ecological inhibition caused by the high alkalinity (pH>9.0) of traditional materials; damage self-repair: when the chitosan gelling agent is eroded by seawater, the amino groups released by the broken molecular chains can form complexes with Ca 2+ to form complexes, which can autonomously repair microcracks (repair rate ≥70%). BRIEF DESCRIPTION OF DRAWINGS
[0030] Figure 1 is a step flow chart of the preparation of the ecological solidified soil for the integrated scour protection and seagrass restoration provided by the embodiment of the present application. DETAILED DESCRIPTION
[0031] In order to make the purposes, features and advantages of the present application more obvious and easy to understand, the present application will be further described in detail below in combination with the drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.
[0032] In the following, the preparation method of the ecological solidified soil for the integrated scour protection and seagrass restoration in the present exemplary embodiment will be further described.
[0033] First, the sea mud (800-1000 parts) with a moisture content of 20%-35% and the calcined coral sand (200-400 parts, particle size 0.5-5 mm) are put into a double-shaft mixer for mixing. The coral sand is calcined at 800-1000℃ to form a porosity ≥40%, a specific surface area ≥15 m 2 / g porous structure, the CaCO3 skeleton adsorbed on its surface combines with active ingredients such as SiO2 and Al2O3 in the sea mud through micro-interfaces, initially building the mechanical skeleton of the solidified soil. Subsequently, modified chitosan gelling agent (50-150 parts) and silicate geopolymer (100-200 parts) are added in stages. The zwitterionic structure of the modified chitosan gelling agent is adsorbed on the surface of the particles in the slurry through electrostatic action, forming a three-dimensional network structure to impart thixotropy and underwater anti-dispersion properties; the silicate geopolymer is synthesized from fly ash and slag through alkali activation, and the resulting Na2O-Al2O3-SiO2-H2O gel synergistically enhances the early strength with chitosan in a seawater environment.
[0034] During the ecological function integration phase, slow-release nutrient ceramsite (100-250 parts) and pretreated seagrass seeds (50-120 parts) were incorporated in stages. The selected seagrass seed species and their required growth conditions are shown in Table 1.
[0035] Table 1 Seagrass species
[0036]
[0037] The slow-release nutrient ceramsite is based on acid-washed and calcined zeolite. It forms a stable release layer by vacuum adsorption of seaweed polysaccharide extract and coating, which can continuously release nitrogen, phosphorus and organic carbon in a high-salt environment. After the seaweed seeds are soaked in a gibberellic acid-chitosan composite liquid, they are mixed and coated with a suspension of nitrogen-fixing bacteria and phosphate-solubilizing bacteria to form a microorganism-chitosan protective layer, which increases the cumulative germination rate of the seeds to ≥80% in 30 days under low light and high salt stress. At the same time, seawater activator (80 to 160 parts) and microbial carrier (20 to 50 parts) are added. The composite sulfate activator in the seawater activator is activated by SO4 2 -With Al in sea mud 3+ The reaction generates a calcium aluminate skeleton, and the protease-lipase complex accelerates the degradation of organic matter to release cementing substances; the microbial carrier uses diatomaceous earth to load nitrogen-fixing bacteria and phosphate-solubilizing bacteria, the extracellular polysaccharides secreted by them can enhance the adhesion between particles and regulate the pH to 7.8-8.3, thereby optimizing the microenvironment for seagrass colonization.
[0038] Finally, the above components and seawater are added to the mixer at a water-to-solid ratio of 0.3 to 0.5. The slurry is initially homogenized by slow stirring for 3 minutes, and then quickly stirred for 5 minutes to form a self-leveling slurry with a slump of 150 to 220 mm. During the pumping construction phase, the self-leveling slurry is transported to the target seabed area through a flexible pressure-resistant pipe at a pressure of 0.3-0.5 MPa. In this process, the three-dimensional network structure of the modified chitosan gelling agent is formed in the seawater Ca 2+under the instant cross-linking effect, a dynamic viscoelastic interface layer (thickness ≥ 2mm) is first formed on the surface layer of the paste, and the zwitterionic characteristics of the interface layer are anchored to the surface of the seed through electrostatic adsorption between the positive charge sites and the negative groups in the chitosan protective layer of the seed surface microorganisms, so that the seed is effectively anchored in the paste; meanwhile, the thixotropic characteristics of the chitosan network make the paste show a transient viscosity drop (apparent viscosity from 15-25 Pa·s to 5-8 Pa·s) under the pumping shear rate, and when the flow rate of the paste decreases suddenly, the viscosity of the paste rapidly recovers to 18-30 Pa·s within 3-5 s, forming a Bingham-like fluid characteristic, which significantly reduces the probability of seed diffusion with water flow.
[0039] After pumping to the seabed, the chitosan gelling agent generates a large amount of Ca 2+ The cross-linking rapidly forms a network structure to inhibit dispersion, and the silicate geopolymer continuously generates a gel phase, which, together with ettringite, builds a scour-resistant skeleton (strength ≥ 1.0 MPa after 28 days). In this process, the slow-release ceramsite gradually releases nutrients, the microbial carrier degrades organic matter to generate CO2 micro-bubbles to create an oxygen-rich germination environment for the seagrass seeds, and the zwitterionic chitosan dynamically adsorbs Cl- and Na + The pore fluid salinity is reduced to ≤ 3.5%, achieving synergistic effect of ecological restoration and scour resistance in a high-salinity environment.
[0040] The following is a specific embodiment of the present application:
[0041] Embodiment one
[0042] The present embodiment provides an ecological restoration method of ecological solidified soil, comprising the following steps:
[0043] (1) Add 900 parts of sea mud with a moisture content of 25% and 300 parts of coral sand calcined at 900°C (particle size 1-3 mm) to a double-shaft mixer, and pre-mix at a speed of 45 rpm for 5 min.
[0044] (2) Add chitosan gelling agent 100 parts and slag-based silicate geopolymer 150 parts step by step.
[0045] (3) Incorporate slow-release nutrient ceramsite 180 parts, coated eelgrass seed 80 parts, seawater activator 120 parts, and diatomite-loaded microbial carrier 35 parts in sequence.
[0046] (4) Add artificial seawater at a water-solid ratio of 0.4, first slow stirring for 3 min, then switch to fast stirring for 5 min, to obtain a self-leveling paste with a slump of 195±5 mm.
[0047] Performance test: The paste was pumped into a simulated seabed environment with a flow rate of 2.8 m / s, water temperature of 15±2℃, salinity of 3.5%, and light intensity of 3000lx. The 28-day compressive strength was 1.2 MPa, the pore fluid pH was 8.0±0.2, and the total germination rate of eelgrass seeds was 86% after 30 days.
[0048]
[0049] wherein n i is the number of seeds germinated on the i-th day, and N is the total number of seeds germinated.
[0050] This example constructs a stable matrix through the synergistic effect of calcined coral sand and chitosan gelling agent. The honeycomb structure formed after high-temperature activation of the coral sand (porosity increased to 48%) effectively improves the aggregate interlocking force, and the silicate network produced by the geopolymer makes the 28-day compressive strength reach 1.2 MPa. It is particularly suitable for the growth needs of eelgrass: this species is suitable for growing in clear water with an intertidal zone to 20 meters deep and a light intensity of more than 1500lx, and the matrix porosity needs to be >40% to facilitate root anchoring. The pore fluid pH is precisely controlled in the critical interval of 8.0±0.2, which is highly consistent with the optimal pH (7.5-8.5) for eelgrass growth. Thanks to the calcium carbonate slow-release buffer mechanism of calcined coral sand, the high alkalinity problem (pH>9.5) of traditional cement-based materials is avoided. The three-dimensional network structure formed by the chitosan gelling agent not only enhances the thixotropy of the paste, but also fixes the eelgrass seeds through electrostatic adsorption due to its positive charge, which increases the 30-day cumulative germination rate to 86%. The slow-release nutrient ceramic combined with the microbial carrier forms a gradient nutrient supply system, and the combination of alginate and protease in the pore fluid synergistically regulates the mineralization rate of organic matter, maintaining microbial activity.
[0051] Example Two
[0052] (1) Add 950 parts of sea mud with a water content of 32% and 350 parts of calcined coral sand (particle size 4-5mm, porosity 48%) to a double-shaft mixer, and pre-mix at a speed of 45rpm for 5 minutes.
[0053] (2) Add chitosan gelling agent 130 parts and fly ash geopolymer 180 parts step by step.
[0054] (3) Add high-porosity slow-release ceramic 220 parts, coated eelgrass seeds 110 parts, seawater activator 160 parts and microbial carrier 40 parts at the same time.
[0055] (4) Inject seawater at a water-solid ratio of 0.48, first slow mixing for 3 minutes, then switch to fast stirring for 5 minutes, to obtain a self-leveling paste with a slump of 195±5mm.
[0056] Performance test: The slurry was pumped into a simulated seabed environment with a flow rate of 2.8 m / s, water temperature of 15±2℃, salinity of 3.5%, and light intensity of 3000lx. The 28-day compressive strength was 1.3 MPa, the pore fluid pH value was 8.1±0.3, and the cumulative germination rate of Thalassia hemprichii seeds was 85% in 30 days.
[0057] This example optimizes the particle size distribution by a staged feeding process, using calcined coral sand (4-5mm) and slow-release ceramic particles to form a graded skeleton. The pore structure shows a bimodal distribution (micropores 10-50μm and interstitial spaces 300-500μm), which not only ensures the compressive strength (1.3MPa) but also provides space channels for the expansion of seagrass root systems. The selected Thalassia hemprichii is adapted to tropical marine areas with intertidal zones to 10 meters deep, salinity of 30-35‰. The system simulates the salinity (3.5%) consistent with the target sea area, and the substrate bulk density is 1.52g / cm 3 , which matches the original coral debris substrate (1.45-1.60g / cm 3 ). The double microbial coating technology realizes seed slow-release germination through chitosan-gibberellic acid composite film, and the online pH monitoring data shows that the pore fluid fluctuation amplitude is controlled within ±0.3, which has significant environmental stability compared with the cement-based material of Comparative Example 3 (pH fluctuation >2.0).
[0058] Comparative Example One
[0059] The formulation of Example One was used but the modified chitosan gelling agent was omitted, only using 200 parts of silicate geopolymer as the gelling material, and the remaining components and process parameters were consistent with Example One.
[0060] Performance test: The slurry was pumped into a simulated seabed environment with a flow rate of 2.8 m / s, water temperature of 15±2℃, salinity of 3.5%, and light intensity of 3000lx. The 28-day compressive strength was 0.38 MPa, the pore fluid pH value was 9.2±0.5, and the cumulative germination rate of Enhalus acoroides seeds was 32% in 30 days.
[0061] The absence of chitosan gelling agent in this comparative example results in a single gelling system, and the sodium silicate produced by the rapid hydration of geopolymer causes the initial pH to rise sharply to 9.2. The high alkaline environment inhibits the activity of nitrogen-fixing bacteria (survival rate drops to 35%), and the lack of organic cement network results in weak aggregate interface bonding, with a sharp 68% drop in compressive strength. The loss rate of seagrass seeds is as high as 68% under the dual action of high pH and the absence of mechanical anchoring, and the microenvironment required for germination is destroyed. Compared with the composite gelling system of Example One, a single inorganic gelling material cannot build a dual protection mechanism of pH buffering and mechanical fixation.
[0062] Comparative Example Two
[0063] The calcined coral sand in Example One was replaced with uncalcined natural coral sand (specific surface area 4m2 / g, porosity 12%), other components and process parameters are the same as example 1.
[0064] Performance test: the slurry was pumped into a simulated seabed environment with a flow rate of 2.8 m / s, water temperature of 15±2℃, salinity of 3.5%, and light intensity of 3000lx. The 28-day compressive strength was 0.72 MPa, the pore fluid pH was 7.6±0.4, and the cumulative germination rate of eelgrass seeds was 41%. The solidified body had 1.8 mm honeycomb pores, and the plant lodging rate was 61.5%.
[0065] When the uncalcined coral sand was used in this comparative example, its original low porosity (12%) resulted in a high aggregate bulk density, and the solidified body formed a dense structure (porosity only 18%), which not only limited the function of the microbial carrier but also weakened the pH regulation ability of calcium carbonate. The passivation layer on the surface of the unactivated coral sand hindered the chemical bonding with the geopolymer, and macro defects of 1.8 mm appeared in the interfacial transition zone, and the plant lodging rate increased to 61.5%. Compared with the calcination process of example 1, high-temperature treatment increased the specific surface area of the coral sand by 12 times (from 4 m 2 / g to 50 m 2 / g), significantly improving its ion exchange capacity and gel activity.
[0066] Comparative example three
[0067] Ordinary P.O 42.5 Portland cement 200 parts was used to replace the geopolymer, and the microbial carrier was removed. The rest of the component ratio was consistent with example 1.
[0068] Performance test: the slurry was pumped into a simulated seabed environment with a flow rate of 2.8 m / s, water temperature of 15±2℃, salinity of 3.5%, and light intensity of 3000lx. The 28-day compressive strength was 0.95 MPa, but the pore fluid pH was 11.2 (caused by cement alkali activation), and the cumulative germination rate of eelgrass seeds was 19.3% in 30 days.
[0069] After using Portland cement in this comparative example, the Ca(OH)2 produced by hydration maintained the pore fluid pH above 11.2 for a long time, leading to lipid peroxidation of eelgrass seed cell membranes (MDA content increased by 3.8 times), and the cumulative germination rate was less than 20% in 30 days. Although the dense structure of cement hydration products brought 0.95 MPa strength, the closed pores blocked the material exchange between the microbial carrier and the environment, and the microbial diversity index decreased by 72%. Compared with the geopolymer system of example 1, traditional cement lacks biocompatibility modification, and the high-alkali environment makes the controlled-release ceramsite lose its control function (12-hour nutrient release rate reached 98.7%), which cannot achieve the continuous supply required for ecological restoration.
[0070] The foregoing primarily describes and shows the main features of the present application and the advantages of the present application. Those skilled in the art should understand that the present application is not limited to the above-mentioned embodiments, and the above-mentioned embodiments and descriptions in the specification are only preferred examples of the present application and are not intended to limit the present application. Various changes and improvements can be made to the present application without departing from the spirit and scope of the present application, and these changes and improvements all fall within the scope of the claimed present application. The scope of protection of the present application is defined by the appended claims and their equivalents.
Claims
1. An ecologically stabilized soil for scour protection and seaweed restoration, characterized in that: The following components are included in parts by weight: Base material: 800-1000 parts of sea mud, with a moisture content of 20%-35%, an organic matter content of 3%-8%, and a pH of 7.5-8.5; 200-400 parts of coral sand, with a particle size of 0.5-5 mm, and a porosity of ≥40% after calcination at 800-1000°C and a specific surface area of ≥15 m 2 / g; Curing agent: 50-150 parts of modified chitosan gelling agent, 100-200 parts of silicate geopolymer; Ecological functional components: 100-250 parts of slow-release nutrient ceramsite, particle size 2-8mm, nitrogen, phosphorus and potassium slow-release period ≥90 days; 50-120 parts of seaweed seeds, cumulative germination rate ≥80% in 30 days; Auxiliary additives: 80-160 parts of seawater activator, 20-50 parts of microbial carrier, the microbial carrier carries nitrogen-fixing bacteria and phosphate-solubilizing bacteria, and the bacterial concentration is ≥1×10 8 CFU / g, loading rate ≥90%.
2. The ecologically solidified soil according to claim 1, characterized in that: The preparation method of the modified chitosan gelling agent comprises: (1) Chitosan with a deacetylation degree of ≥85% was dissolved in a 2% acetic acid solution, and maleic anhydride was added at a chitosan to maleic anhydride molar ratio of 1:0.15-0.
25. The mixture was reacted at 50-60°C for 4-6 hours, and then dialyzed and freeze-dried to obtain carboxylated chitosan. (2) Carboxylated chitosan and glycidyl trimethylammonium chloride were reacted at a molar ratio of 1:0.3-0.5 at pH 8.0-8.5 for 12-24 hours to prepare a zwitterionic chitosan gelling agent.
3. The ecologically solidified soil according to claim 1, characterized in that: The silicate geopolymer is prepared by mixing fly ash and slag in a mass ratio of 2:1 and then grinding the mixture to a specific surface area of 400m 2 / kg, add 8-12 mol / L NaOH solution, liquid-to-solid ratio 0.3-0.5, stir and solidify at 50-70℃ for 12-24 hours, steam cure at 60℃ for 48 hours, and crush to particle size ≤100μm.
4. The ecologically solidified soil according to claim 1, characterized in that: The preparation method of the slow-release nutrient ceramsite comprises: (1) Crushing natural zeolite into 1-3 mm, soaking it in 5% hydrochloric acid for 2 hours, washing it with water until it is neutral, calcining it at 600℃ for 2 hours, and obtaining a specific surface area of ≥300m 2 / g porous skeleton; (2) crushing the brown algae and mixing it with deionized water at a ratio of 1:10, adding 0.5% w / w cellulase, enzymatically hydrolyzing at 50°C for 4 hours, and centrifuging and concentrating to a solid content of ≥20% to obtain a seaweed polysaccharide extract; (3) Zeolite and seaweed extract were vacuum adsorbed at a mass ratio of 1:1.5 for 30 minutes, dried at 80°C, and then instantaneously calcined at 300°C for 5-10 minutes to form a stable coating layer.
5. The ecologically solidified soil according to claim 1, characterized in that: The seaweed seed pretreatment comprises: (1) Select eelgrass (Zostera marina), Thalassia hemprichii, or Halophila ovalis seeds with a seed size of 1.5 to 3.0 mm and a retention density of ≥1.1 g / cm2 using a 3% NaCl solution sedimentation method. 3 living seeds. (2) Soak the seeds in a 100 mg / L gibberellic acid and 0.1% chitosan complex solution at 25°C in the dark for 24 hours and dry until the moisture content is ≤8%; (3) Mix the seeds with nitrogen-fixing bacteria / phosphate-solubilizing bacteria suspension (bacteria concentration ≥ 1×10 8 CFU / mL) were mixed and coated at a mass ratio of 1:2, with a coating rate of ≥15%.
6. The ecologically solidified soil according to claim 1, characterized in that: The seawater activator comprises: (1) Sodium sulfate and calcium sulfate are mixed in a mass ratio of 3:1 and ground to a particle size of ≤50 μm, and calcined at 400-500° C. for 2 hours to generate a composite sulfate activator with a SO 3 content of ≥35%; (2) Protease and lipase were compounded at an enzyme activity of 5000U / g + 3000U / g and spray-dried with sulfate activator at a mass ratio of 1:
5.
7. The ecologically solidified soil according to claim 1, characterized in that: The preparation method of the microbial carrier comprises: (1) Soak diatomite in 10% hydrochloric acid for 4 hours and calcine at 600℃ for 3 hours to form a porosity of ≥60% and a specific surface area of ≥200m 2 / g of carrier; (2) The nitrogen-fixing bacteria and the phosphate-solubilizing bacteria were mixed in a bacterial liquid volume ratio of 1:1, and adsorbed with diatomaceous earth in a mass ratio of 1:2 by oscillation for 6 hours, and dried in a vacuum at 40°C. The loading rate was ≥90%.
8. A construction method for ecologically solidified soil according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Put the base material, curing agent, ecological functional components and auxiliary additives into a mixer, inject seawater at a water-solid ratio of 0.3 to 0.5, and stir to form a self-leveling slurry with a slump of 150 to 220 mm and a fluidity of ≥180 mm; (2) The slurry is transported to the seabed by pumping equipment, with an initial setting time of 6 to 12 hours, a compressive strength of ≥0.3 MPa after 7 days, a strength of ≥1.0 MPa after 28 days, and an anti-scour velocity of ≥2.5 m / s; (3) The cumulative germination rate of seagrass shall be ≥80% within 30 days of construction, and a stable meadow with a vegetation coverage rate of ≥70% shall be formed within 90 days.
9. The construction method according to claim 8, characterized in that: The slurry pumping flow rate is 0.5 to 1.2 m 3 / min, pumping pressure ≤0.5MPa, daily construction area reaches 500-800m 2 .
10. The construction method according to claim 8, characterized in that: The solidified soil forms a porous skeleton with a porosity of 25% to 35% on the seabed, a pore fluid salinity of ≤3.5%, and a carbon storage capacity of ≥50kg / m 3 .
11. The ecologically solidified soil according to claim 1, characterized in that: The synergistic effect of the base material and the curing agent maintains the pH of the pore fluid of the cured soil at 7.8 to 8.3, which satisfies the optimal acid-base environment for germination and growth of seaweed seeds. (1) The residual alkalinity of the NaOH solution in the silicate geopolymer reacts with the CaO component of the coral sand calcination product to generate Ca(OH)2, which dynamically neutralizes the acidified residue of chitosan; (2) The porous zeolite framework in the slow-release nutrient ceramsite adsorbs excess OH- through ion exchange, stabilizing the pore fluid pH fluctuation to ≤±0.3; (3) The silanol (Si-OH) on the surface of diatomaceous earth in the microbial carrier and the sulfate in the seawater activator form a pH buffer system to maintain a balance between microbial activity and seed germination requirements.
Citation Information
Cited By
Tunnel crack repairing material containing modified marine sludge carrier and preparation method
CN122233726A
A tunnel crack repair material containing modified marine silt carrier and its preparation method
CN122233726B